Genotype-specific effects of elamipretide in patients with primary mitochondrial myopathy: a post hoc analysis of the MMPOWER-3 trial - Amel Karaa; Enrico Bertini; Valerio Carelli; Bruce Cohen; Gregory M. Ennes; Marni J. Falk; Amy Goldstein; Gráinne Gorman; Richard Haas; Michio Hirano; Thomas Klopstock; Mary Kay Koenig; et al. (Orphanet Journal of Rare Diseases)
Abstract Background As previously published, the MMPOWER-3 clinical trial did not demonstrate a significant benefit of elamipretide treatment in a genotypically diverse population of adults with primary mitochondrial myopathy (PMM). However, the prespecified subgroup of subjects with disease-causing nuclear DNA (nDNA) pathogenic variants receiving elamipretide experienced an improvement in the six-minute walk test (6MWT), while the cohort of subjects with mitochondrial DNA (mtDNA) pathogenic variants showed no difference versus placebo. These published findings prompted additional genotype-specific post hoc analyses of the MMPOWER-3 trial. Here, we present these analyses to further investigate the findings and to seek trends and commonalities among those subjects who responded to treatment, to build a more precise Phase 3 trial design for further investigation in likely responders. Results Subjects with mtDNA pathogenic variants or single large-scale mtDNA deletions represented 74% of the MMPOWER-3 population, with 70% in the mtDNA cohort having either single large-scale mtDNA deletions or MT-TL1 pathogenic variants. Most subjects in the nDNA cohort had pathogenic variants in genes required for mtDNA maintenance (mtDNA replisome), the majority of which were in POLG and TWNK. The mtDNA replisome post-hoc cohort displayed an improvement on the 6MWT, trending towards significant, in the elamipretide group when compared with placebo (25.2 ± 8.7 m versus 2.0 ± 8.6 m for placebo group; p = 0.06). The 6MWT results at week 24 in subjects with replisome variants showed a significant change in the elamipretide group subjects who had chronic progressive external ophthalmoplegia (CPEO) (37.3 ± 9.5 m versus − 8.0 ± 10.7 m for the placebo group; p = 0.0024). Pharmacokinetic (exposure–response) analyses in the nDNA cohort showed a weak positive correlation between plasma elamipretide concentration and 6MWT improvement. Conclusions Post hoc analyses indicated that elamipretide had a beneficial effect in PMM patients with mtDNA replisome disorders, underscoring the importance of considering specific genetic subtypes in PMM clinical trials. These data serve as the foundation for a follow-up Phase 3 clinical trial (NuPOWER) which has been designed as described in this paper to determine the efficacy of elamipretide in patients with mtDNA maintenance-related disorders. Classification of evidence Class I ClinicalTrials.gov identifier NCT03323749